Predictors of Immunosuppressive Regulatory T Lymphocytes in Healthy Women. (26th August 2012) - Hampras, Shalaka S.; Nesline, Mary; Wallace, Paul K.; Odunsi, Kunle; Furlani, Nicholas; Davis, Warren; Moysich, Kirsten B.
Abstract : Immunosuppressive regulatory T (Treg) cells play an important role in antitumor immunity, self-tolerance, transplantation tolerance, and attenuation of allergic response. Higher proportion of Treg cells has been observed in peripheral blood of cancer cases compared to controls. Little is known about potential epidemiological predictors of Treg cell levels in healthy individuals. We conducted a cross-sectional study including 75 healthy women, between 20 and 80 years of age, who participated in the Data Bank and BioRepository (DBBR) program at Roswell Park Cancer Institute (RPCI), Buffalo, NY, USA. Peripheral blood levels of CD4 + CD25 + FOXP3 + Treg cells were measured using flow cytometric analysis. A range of risk factors was evaluated using Wilcoxon Rank-Sum test, Kruskal-Wallis test, and linear regression. Age, smoking, medications for treatment of osteoporosis, postmenopausal status, body mass index (BMI), and hormone replacement therapy (HRT) were found to be significant positive predictors of Treg cell levels in peripheral blood (P ≤ 0.05 ). Higher education, exercise, age at first birth, oral contraceptives, and use of Ibuprofen were found be significant (P < 0.05 ) negative predictors of Treg levels. Thus, various epidemiological risk factors might explain interindividual variation in immune response to pathological conditions, including cancer.